HUBUNGAN TINGKAT KEPERCAYAAN DIRI DENGAN OBESITAS PADA SISWA SMA REX MUNDI MANADO - Rupang, Indra; Opod, H.; Sinolungan, Jehosua (eBiomedik, 2013)
Abstract: Obesity is an increase in body weight exceeds the limit of skeletal and physical requirements as a result of the accumulation of excess fat in the body. In the adolescents, obesity will also affect the psychosocial development including self-confidence. Adolescent obesity is shunned by her/his friends have a tendency to have low self esteem and a sense of pessimism. Self esteem is a belief to be able to behave as expected and desired. The research aimed to know the correlation self esteem in students who are obese at Rex Mundi High School Manado. This research uses retrospective observational study with cross-sectional (cross-sectional) with samples 50 people. Sampling in this study was purposive sampling. Measurement tool that was used is the self esteem scale with reliability (?) = 0.896. Then all collected data were analyzed using Pearson Product Moment Correlation which supported by SPSS 20 program for windows. The results showed the self esteem in obese adolescents who are in the moderate category 26 peoples (52%). According to Pearson analysis, the result are r =  -0.676 and p = 0.000. This indicates that there is a negative correlation between self-esteem and obesity at significance level 0.05. Negative correlation means, if the variable X increases, the variable Y decreases. So the higher the obesity rate, the lower the students' confidence. Keywords: Obesity, Self-Esteem.  Abstrak: Obesitas adalah peningkatan berat badan melebihi batas kebutuhan skeletal dan fisik sebagai akibat akumulasi lemak berlebihan dalam tubuh. Pada kelompok remaja, obesitas akan berpengaruh pula pada perkembangan psikososial termasuk kepercayaan diri. Remaja obesitas yang dijauhi oleh teman-temannya memiliki kecenderungan untuk mengalami kepercayaan diri yang rendah dan rasa putus asa yang besar. Kepercayaan diri merupakan suatu keyakinan seseorang untuk mampu berperilaku sesuai dengan yang diharapkan dan diinginkan. Penelitian ini bertujuan untuk melihat hubungan tingkat kepercayaan diri pada siswa yang mengalami obesitas di SMA Rex Mundi Manado. Penelitian ini merupakan restrospektif observasional dengan rancangan cross sectional (potong lintang) dengan jumlah sampel 50 orang. Pengambilan sampel menggunakan purposive sampling. Alat ukur yang digunakan adalah skala kepercayaan diri dengan reliabilitas (?) = 0,896. Metode analisis data dilakukan dengan teknik korelasi Pearson Product Moment menggunakan program SPSS 20 for windows. Hasil penelitian menunjukkan tingkat kepercayaan diri pada remaja yang obesitas berada pada kategori sedang sebanyak 26 orang (52%). Hasil analisis data diperoleh hasil r = -0,676 dan p = 0,000. Hal ini menunjukkan bahwa terdapat hubungan negatif antara kepercayaan diri dengan obesitas pada taraf signifikansi 0,05. Hubungan negatif berarti, jika variabel X meningkat maka variabel Y menurun. Jadi semakin tinggi tingkat obesitas siswa maka semakin rendah kepercayaan dirinya. Kata Kunci: Obesitas, Kepercayaan Diri.